The administration of Bona Vacantia (Ownerless Property) in West Malaysia: a comparative analysis - Mohd Yusoff, Rahmawati; Halim, Akmal Hidayah; Azlan, Wan Amir; Arshad, Azhani; Ali, Alizah; Ismail, Noraini; Ghazali, Ahmad Faiz; Sainan, Zuramaznum (Human Resource Management Academic Research Society (HRMARS), 2021)
The terms bona vacantia and ownerless property have been used interchangeably which refers to assets or goods that do not have an owner. Every year, the number of unclaimed estates in Malaysia is constantly rising and the call for a better regulation and management of bona vacantia estates has never been more important. This paper aims to enhance the administration of bona vacantia in west Malaysia by referring Singapore and the United Kingdom in light of potential for cross‐jurisdictional use of the framework. The doctrinal analysis was adopted by analysing the current primary and secondary materials which includes statutory provisions, journal articles, books and other legal and non-legal literatures. The study finds key features of each of the jurisdiction as well as important similarities and differences that could be useful to be implemented in Malaysia. As a recommendation Malaysian authority may take advantage on interest payment for any claim made by the beneficiary up to certain years in order to encourage beneficiaries to cooperate together to claim the estates in question immediately. Further, by introducing Unclaimed Estates Websites may be able to provide accessibility of information and platform for long lost beneficiaries or relatives to meet up virtually.